Sufi Dance Performativity of Maulana Rumi Islamic Boarding School in Yogyakarta - Heni Siswantari; Lovandri Dwanda Putra; Fatih Ridlwan Munier; Ucik Wulandari (Universitas Negeri Semarang, 2023)
Sufi dance is one of the dances that is considered the most Islamic and represents spiritual values. One of the Islamic boarding schools that is still developing Sufi dance is Maulana Rumi Islamic Boarding School, Yogyakarta. The method used is qualitative with a performance studies approach in Sufi dance. The collection techniques are observation, interviews, and documentation. Obtaining survey data uses a multidisciplinary approach; art-social science, and art-religion. While the data analysis technique uses the opinion of Milles & Huberman, namely data collection- data reduction- data presentation- conclusion. The results showed that the performance of Sufi dance at Maulana Rumi Islamic Boarding School are as follows: (1) Sufi dance performance is carried out routinely every selapanan night or once every 40 days at Maulana Rumi Islamic boarding school. Another event that is also regularly held is the Sufi dance performance in the study which is held at Basa Basi cafe in Yogyakarta every Wednesday from 20.00-22.00 WIB. Sufi dance performances are performed in between recitations of books both by Maulana Rumi and others, such as the book Ihya Ulumuddin by Imam Gozali, the book Nurudh Dholam by Syekh Muhammad Nawawi As-Syafi'ie, and the book Hidayatul Azkiya Ila Thariqil Auliya by Zeinuddin ibn Ali Al-Ma' Bari Al-Malibari. (2) There is a social interaction between dancers and study participants who are both present in the same space and time at the Maulana Rumi Islamic boarding school and the Basa Basi cafe, and (3) The Sufi dance performance events were manifested by an interrelationship between dancers and performers where the audience feels involved in spiritual events in the form of the Sufi dance.